Use of the Agricultural Competitiveness Enhancement Fund (ACEF) by the Department of Agriculture - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2012)
The Agricultural Competitiveness Enhancement Fund (ACEF) is an ongoing loan and grant program in the Philippines for agriculture and fisheries. From the start of its actual implementation in 2000 up to the present, it has been plagued by numerous problems which significantly derailed the attainment of its objectives. Because of this, its implementation was suspended in 2011 and an evaluation was conducted in line with the zero-based budgeting (ZBB) approach of the national government. As the output of the evaluation, this study reviewed the ACEF program, identified and analyzed the fund management and other pressing problems and issues it is facing, and provided options as well as specific recommendations for effectively addressing them. The study concluded that since ACEF is a big public expenditure item, it is imperative for the national government to immediately act on its numerous problems by implementing positive changes. It argued that without meaningful reforms, ACEF may just go down as one of the greatest national program failures in recent memory.
Keywords: 330; Philippines; agriculture; small and medium enterprises (SMEs); zero-based budgeting; Agricultural Competitiveness and Enhancement Fund (ACEF); fisheries; low loan repayment rates; internationally competitive products; Landwirtschaftsbank; Agrarkredit; Entwicklungsfinanzierung; KMU; Internationaler Wettbewerb; Philippinen